Perlindungan Hukum Terhadap Hutan Mangrove Pada Areal Pesisir Pantai - Ricky Marthin Wattimena; Wilshen Leatemia; Lucia Charlota Octovina Tahamata (Balobe Law Journal, 2021)
Introductioan: One of the potentials of mangrove forests is to prevent coastal abrasion. With the existence of mangrove forests, erosion of coastal areas during the rainy season can be minimized. Besides that, mangroves can also be an ecosystem for crabs and various other types of fish. However, in the course of development, many times mangrove forests are converted and also destroyed because of development interests by individuals and development companies.Purposes of the Research: The purpose of this article is to find out how to regulate the management of coastal areas and how to protect the law against mangrove forest areas on the coast of Piru Village, West Seram Regency.Methods of the Research: This research is a normative research using a statutory approach with sources of legal materials used are primary legal materials, secondary legal materials and tertiary legal materials with qualitative analysis.Results of the Research: The results of the study found that the regulation related to the management of coastal areas is regulated in Law No. 1 of 2014 and in its implementation in the field there is still damage to mangrove forests, especially in the coastal area of Piru Village, West Seram Regency and is detrimental to coastal communities because the coastal area is an area that should protected because it is important for the sustainability of the community in the area.